The ability of layered double hydroxides for nitrate absorption and desorption in crop and fallow rotation - M. Mohammadi; A. Mohammadi Torkashvand; P. Biparva; M. Esfandiari (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: This study aims down to evaluate the ability of chloride magnesium- aluminium- layered double hydroxides (4:1) for nitrate adsorption from the soil solution in successive cropping periods. METHODS: The study was conductedunder long-term cropping periods, including first crop): bell pepper; second crop: mentheae; third crop: cherry tomato; and fort h crop: wheat), absorption of soil mineral nitrate in fallow periods and nitrate absorption from plants by layered double hydroxides. The effect of layered double hydroxides on qualitative and quantitative characteristics of plants was also studied. FINDING: Results indicated that layered double hydroxides were able to induce long-term nitrate exchange in crop and fallow sequences. Layered double hydroxides can adsorb soil excessive nitrates in cropping periods and reduce nitrate concentration in the soil solution. Compared to control, the treatment with 16 gram layered double hydroxide/kilogram soil could reduce nitrate concentration in the soil solution by 95%. During two-week fallow periods, the amount of nitrates mineralized in the soil solution was increased, but layered double hydroxides treatments could adsorb them well and maintained the N-nitrate concentration in the soil solution at a low level. Additionally, Results indicated that application of 2, 4, 8 and 16 gram layered double hydroxides/kilogram soil led to 34%, 44%, 58% and 69% reduction in N-nitrate concentration of soil leachates, respectively, compared to control. By increasing nitrogen availability, layered double hydroxides improved the quantitative and qualitative properties of plants. Application of 2, 4, 8 and 16 gram layered double hydroxides/ kilogram soil increased the plant height (cherry tomato) by 14%, 26%, 50% and 80%, respectively. CONCLUSION: It is concluded that the layered double hydroxides has a potential to be used as a long-term nitrate exchanger to control the movement of nitrate in soil, and thereby reduce risks of nitrate leaching in crop production in sensible areas.